IMPACT OF WEIGHT LOSS ON LAMENESS ASSOCIATED WITH HIP OSTEOARTHRITIS IN OBESE DOGS - Rashmi Verma; Sujata Turkar; APS Sethi (Exploratory Animal and Medical Research, 2022)
The present clinical study was conducted in ten Labrador retriever obese dogs with lameness associated with hip osteoarthritis to evaluate the effect of weight loss on its management. The weight loss protocol involved feeding of high protein and low-fat diet (for 90 days) along with conservative therapy (for 30 days) to assess the effect of these interventions on lameness, quality of life, haemato-biochemical parameters and subcutaneous fat thickness in obese dogs. After 90 days of feeding weight loss diet, dogs achieved on an average 6.5 % body weight loss at the rate of 0.5% weight loss per week. Body condition score, lameness scores (Numeric Rating Scale, NRS and Visual Analogue Scale, VAS) and quality of life showed significant improvement at the end of the study. Subcutaneous fat thickness significantly reduced from mid abdomen and chest on day 30, day 60 and day 90. The mean haemoglobin and packed cell volume increased significantly, whereas mean relative neutrophil counts decreased significantly on day 30, day 60, day 90 as compared to day 0. The mean serum cholesterol, calcium and C-reactive protein concentrations also decreased significantly.